Evaluating the Potential of two Invasive Plant Species as Sustainable Substrate for Oyster Mushroom (Pleurotus Spp.) Cultivation in Nepal - Bhandari, Prabha; Adhikari, Alina; Kafley, Manoj; Lamichhane, Nabin; Koirala, Niranjan; Aryal, Hari Prasad (Himalayan Biodiversity, 2025)
Oyster mushroom (Pleurotus spp.) is one of the most commonly cultivated mushrooms in Nepal due to its adaptability to a wide range of substrates. This study evaluates the potential of invasive plant species, Lantana camara and Parthenium hysterophorus, as substrates for oyster mushrooms (Pleurotus sp.) cultivation compared to traditional substrates such as rice straw and sawdust. The results show significant variations in mushroom weight, height, and cap width across substrates. Lantana camara substrate yielded a mean mushroom weight of 238.1 ± 21.1 g, height of 3.5 ± 0.8 cm, and cap width of 2.9 ± 0.7 cm, while Parthenium hysterophorus yielded 176.2 ± 37.6 g, 2.6 ± 1.2 cm, and 1.7 ± 0.6 cm, respectively, on 2 kg of substrates. Traditional substrates performed better, with rice straw producing a mean weight of 529.2 ± 39.8 g, height of 2.6 ± 0.9 cm, and cap width of 2.1 ± 0.7 cm, while sawdust produced the highest mean weight (558.4 ± 301.4 g), tallest mushrooms (7.1 ± 1.6 cm), and largest cap width (5.7 ± 0.5 cm). One-way ANOVA confirmed a significant effect of substrate on mushroom weight (F = 8.183, p = 0.002), height (F = 16.82, p < 0.001), and cap width (F = 40.47, p < 0.001). Pairwise comparisons showed that sawdust consistently supported the tallest mushrooms and largest cap width, while rice straw also performed significantly better than Lantana camara and Parthenium hysterophorus in mushroom weight. Principal component analysis (PCA) revealed that PC1 (79.7% variance) was driven by mushroom height and cap width, while PC2 (18.6% variance) was influenced by mushroom weight. This study demonstrates that invasive species like Lantana camara and Parthenium hysterophorus produce some amount of oyster mushroom, however, traditional substrates remain superior as compared to these IAPS.